2000
DOI: 10.4269/ajtmh.2000.62.639
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological and virological influenza survey in Dakar, Senegal: 1996-1998.

Abstract: Abstract. An influenza survey was conducted in seven sentinel sites in Dakar, Senegal from June 1996 to December 1998. Throat or nasal swab cultures were randomly collected from 804 patients suffering from influenza-like symptoms. Influenza viruses were isolated at a similar proportion in adults and in children (P ϭ 0.29). Strains of influenza B viruses were isolated from sporadic cases in 1997, whereas type A virus was associated with an isolated peak. Proportions of influenza virus isolation varied from 17.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
50
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 3 publications
8
50
1
Order By: Relevance
“…Some other studies of influenza activity in tropical and subtropical countries have also a observed proportional association with humidity (Dosseh et al, 2000;Tang et al, 2010). In addition, Tamerius et al (2013) report that in regions where specific humidity and temperature remain high, influenza peaks occurred during humid-rainy conditions.…”
Section: Discussionmentioning
confidence: 89%
“…Some other studies of influenza activity in tropical and subtropical countries have also a observed proportional association with humidity (Dosseh et al, 2000;Tang et al, 2010). In addition, Tamerius et al (2013) report that in regions where specific humidity and temperature remain high, influenza peaks occurred during humid-rainy conditions.…”
Section: Discussionmentioning
confidence: 89%
“…A selection of the influenza-positive specimens was chosen for virus isolation attempts based on the real-time RT-PCR positive (lowest Ct values), timing (taking into account periods of detection for a better coverage), and country of sampling. Samples were inoculated onto monolayers of Madin-Darby canine kidney (MDCK) cells with a maintenance media supplemented with 2 μg/mL trypsin (TPCK; reference 93630; Sigma-Aldrich) as described previously 6 and incubated at 35 C for 3-7 days with daily monitoring of cytopathic effects (CPEs) by microscopy. After this step, tissue-culture fluids were harvested and screened for influenza virus by hemagglutination (HA) titration.…”
Section: Methodsmentioning
confidence: 99%
“…In Africa, surveillance schemes have been implemented in a very small number of countries such as Senegal [10], Ivory Coast [11] and Madagascar [12][13][14][15]. In these countries, IV circulation and ILI incidence were demonstrated to vary according to the climate and geographical position of the particular country.…”
Section: Introductionmentioning
confidence: 99%